2021
DOI: 10.1007/s00125-021-05428-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of overlapping genetic association in type 1 and type 2 diabetes

Abstract: Aims/hypothesis Given the potential shared aetiology between type 1 and type 2 diabetes, we aimed to identify any genetic regions associated with both diseases. For associations where there is a shared signal and the allele that increases risk to one disease also increases risk to the other, inference about shared aetiology could be made, with the potential to develop therapeutic strategies to treat or prevent both diseases simultaneously. Alternatively, if a genetic signal co-localises with dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…There is increasing evidence for a shared and complex genetic basis for type 1 diabetes, type 2 diabetes and obesity [35]. For example, the SNP in TCF7L2 is considered to be a strong risk factor for type 2 diabetes and was recently also linked to increased risk for type 1 diabetes, primarily in adolescents aged 12 years or older [36].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence for a shared and complex genetic basis for type 1 diabetes, type 2 diabetes and obesity [35]. For example, the SNP in TCF7L2 is considered to be a strong risk factor for type 2 diabetes and was recently also linked to increased risk for type 1 diabetes, primarily in adolescents aged 12 years or older [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found a shared genetic risk factor underlying T1D and T2D etiology (25,26), with approximately 60 chromosome regions associated with T1D ( 27) and over 200 associated with T2D ( 28), reaching genome-wide significance. Therefore, uncovering co-localizing signals could provide biological insights into overlapping disease mechanisms, and potentially reveal therapeutic targets effective for both diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, islet sQTLs can also be considered to understand genetic variants that modify autoimmune T1D risk. The genetic risk for T1D is largely mediated through effects on immune cells 51,52 , although recent studies have highlighted a role of genes expressed pancreatic exocrine and endocrine cells in T1D pathophysiology [53][54][55][56] . We identified examples of islet splicing QTLs at MEG3 lncRNA and ESYT1 that co-localize with T1D association signals 55 (Supplementary Figure 8a,b) and thereby expose new candidate biological mediators for T1D.…”
Section: Discussionmentioning
confidence: 99%